Quantifying the Benefit of Prehospital Rapid Treatment in Acute Stroke: Benchmark for Future Innovative Clinical Trials. Issue 11 (November 2015) - Lorenz, Matthias W.; Lauer, Arne; Foerch, Christian
Abstract : Background and Purpose—: In acute ischemic stroke, time from onset to tissue-type plasminogen activator treatment (OTT) is a major determinant of outcome. To reduce OTT, clinical trials have been undertaken evaluating prehospital cerebral imaging with mobile computed tomographic scanners. Furthermore, blood biomarkers may allow rapid differentiation between ischemic stroke and intracerebral hemorrhage before hospital admission. How such treatment strategies translate into clinical benefit has not been specifically evaluated. Methods—: We constructed decision models to estimate the net clinical benefit yielded by shorter OTT. In different scenarios, we estimated the proportion of patients with favorable outcome and the average quality of life. Results—: An OTT reduction of 60 minutes increases the probability of favorable outcome by 6.6% in a mixed stroke population. For comparison, the average effect of tissue-type plasminogen activator itself is 7.0%. Prehospital mobile computed tomography gaining 25 to 40 minutes increases the probability of favorable outcome by 3.0% to 4.6%. The additional benefit of prehospital computed tomography to deliver patients with large vessel occlusion directly to endovascular treatment centers increases the probability of favorable outcome by another 0.2% to 1.0%. A blood test discriminating ischemic stroke and intracerebral hemorrhage may beneficially substitute brain scan before tissue-type plasminogen activator if >32 to 40 minutes are gained and if sensitivity for intracerebral hemorrhage is >75% to 80%. Conclusions—: Reducing the OTT has robust beneficial effects for acute stroke patients. Prehospital tissue-type plasminogen activator treatment without brain imaging may become conceivable under several preconditions, including a point-of-care test with >75% to 80% sensitivity to detect intracerebral hemorrhage and a time gain of >32 to 40 minutes. Ethical implications remain to be addressed. Abstract : Supplemental Digital Content is available in the text.